2019
DOI: 10.1002/anie.201813417
|View full text |Cite
|
Sign up to set email alerts
|

Z‐Scheme 2D/2D Heterojunction of Black Phosphorus/Monolayer Bi2WO6 Nanosheets with Enhanced Photocatalytic Activities

Abstract: Black phosphorus (BP), a star‐shaped two‐dimensional material, has attracted considerable attention owing to its unique chemical and physical properties. BP shows great potential in photocatalysis area because of its excellent optical properties; however, its applications in this field have been limited to date. Now, a Z‐scheme heterojunction of 2D/2D BP/monolayer Bi2WO6 (MBWO) is fabricated by a simple and effective method. The BP/MBWO heterojunction exhibits enhanced photocatalytic performance in photocataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
195
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 492 publications
(201 citation statements)
references
References 42 publications
4
195
0
2
Order By: Relevance
“…Thewidespread use of semiconductor photocatalysts and clean solar energy is considered an effective strategy to address current environmental and energy crises. [1] Traditional semiconductor metal oxides such as stannic oxide (SnO 2 ), ceric dioxide (CeO 2 ), zinc oxide (ZnO), and titanium dioxide (TiO 2 )a re wide-band-gap photocatalysts and only absorb ultraviolet (UV) light, which greatly limits their photocatalytic efficiency and practical applications. [2] Today, because of their excellent optical absorption properties, suitable band gaps,and unique electronic structure,numerous metal sulfides are attracting considerable research attention as visible-light-response catalysts for environmental purification and solar energy conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Thewidespread use of semiconductor photocatalysts and clean solar energy is considered an effective strategy to address current environmental and energy crises. [1] Traditional semiconductor metal oxides such as stannic oxide (SnO 2 ), ceric dioxide (CeO 2 ), zinc oxide (ZnO), and titanium dioxide (TiO 2 )a re wide-band-gap photocatalysts and only absorb ultraviolet (UV) light, which greatly limits their photocatalytic efficiency and practical applications. [2] Today, because of their excellent optical absorption properties, suitable band gaps,and unique electronic structure,numerous metal sulfides are attracting considerable research attention as visible-light-response catalysts for environmental purification and solar energy conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the 2D/2D BP/Bi 2 WO 6 Z‐Scheme heterojunction was prepared by Lu et al. through stirring BP and Bi 2 WO 6 nanosheets in NMP solution overnight and used for photocatalytic water splitting to produce H 2 and NO removal to purify air (Figure b) . It was found that an intimate interface heterojunction was formed between the 2D BP and Bi 2 WO 6 nanosheets.…”
Section: Diverse Bp‐based Semiconductor Heterojunctionsmentioning
confidence: 99%
“…Notably, the direct Z‐Scheme system can effectively restrain the backward reactions, high fabrication cost, and the light‐shielding effect caused by the electron mediators. Up to now, some BP‐based direct Z‐Scheme systems (BP/BiVO 4 , BP/Bi 2 WO 6 , BP/TiO 2 , and BP/RP) have been developed for photocatalytic water splitting.…”
Section: Diverse Bp‐based Semiconductor Heterojunctionsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Schematic diagram for the visible and NIR light driven photocatalytic H 2 evolution reaction over BP/CN catalyst [29] 无 机 材 料 学 报 第 [34] Fig. 6 Schematic illustration of the mechanism of CdS and BP hybrid catalyst for photocatalytic water splitting [34] Z 型异质结通过控制界面的载流子迁移使低能 量的光生电子与空穴直接复合, 保留高能量的光生 电子-空穴, 从而大大提高了光催化效率。Hu 等 [35] 制备了 BP/单层 Bi 2 WO 6 的 2D/2D Z 型异质结。这 种 BP/Bi 2 WO 6 异质结在光催化分解水制氢方面表现 出较好的光催化性能。BP/Bi 2 WO 6 的最高产氢速率 为 21042 μmol•g −1 , 是 Bi 2 WO 6 的 9.2 倍。 BP/Bi 2 WO 6 异质结具有良好的光催化性能, 主要归功于 2D/2D 异质结的界面协同效应、高效的电荷分离和转移以 及强的吸光性 [35] 。此外, 通过上转换材料与 BP 复 合的方式可增强催化剂对近红外光的利用。Zhang 等 [36] 合 成 了 BP 修 饰 的 三 维 β-NaYF 4 : Yb 3+ , Tm 3+ @Ag 3 PO 4 微棒(NYF@Ag 3 PO 4 @BP), 并将其作 为一种高效的近红外光响应的 Z 型光催化剂。在 980 nm 的激光照射下, NaYF 4 :Yb 3+ ,Tm 3+ 上转换材料 能将 980 nm 的激光转化为可见光和紫外光, 并被 Ag 3 PO 4 和 BP 利用。 NYF@Ag 3 PO 4 @BP 复合材料在 析氢过程中表现出更高的光催化活性, 其产氢速率 比 BP 高 10 倍, 比 NYF@BP 高 6 倍。这种复合材料 的 Z 型电子迁移机制提升了光生载流子的分离效率, 增强了氧化还原能力, 从而提高了光催化活性 [36] 。 石墨烯是一种具有高比表面积和载流子迁移率 的二维材料。石墨烯/BP 复合材料可作为一种高效 的分解水光催化剂 [37] 。 在 Pt 纳米粒子和还原石墨烯 氧化物(RGO)、 BP 纳米片存在的条件下, BP/Pt/RGO 体系在>420 nm 的可见光和>780 nm 的近红外光下 光照 4 h 后分别得到约 5.13 和 1.26 μmol 的 H 2 , 而 且在(420±5)和(780±5) nm 处的 AQE 分别为 8.7%和 1.5%。Pt/RGO 与 BP 纳米粒子之间存在有效的电荷 分离和迁移, 有助于提升可见光和近红外光下的产 氢效率 [37] 。此外, 二硫化钼(MoS 2 )-BP/氧化石墨烯 (GO)的三元光催化剂在光催化分解水制氢反应中 也具有良好的应用前景 [38] , 在可见-近红外光照射 下的光催化产氢活性达到了 3.47 μmol•h −1 , 比 BP/GO 和 MoS 2 -BP 分别提高了 13.3 和 2.27 倍。 GO 在此具 有双重功能: 一方面, GO 在合成过程中充当表面活 性剂和催化剂载体, 有利于促进 BP 的剥离以及 MoS 2 助催化剂在 BP/GO 表面上的修饰; 另一方面, 由于其局部共轭芳族体系和良好的电子穿梭能力, GO 在光催化反应过程中有效地促进了电荷的分离 和转移, 从而提高了光催化产氢性能 [38] 。 等离子共振光催化剂在光催化分解水中也具有 重要应用。利用 Au 纳米颗粒的等离子体共振(SPR) 和 2D-BP 较宽广的带隙范围(0.3~2.1 eV), 可对 La 2 Ti 2 O 7 (LTO)进行敏化 [39] 。 在可见光(>420 nm)和近 红外光(>780 nm)的激发下, BP-Au/La 2 Ti 2 O 7 的产氢 速率可达 0.74 和 0.30 mmol•h −1 •g −1 。 如图 7 所示, Au 图 7 BP-Au/LTO 在(a)可见光和(b)近红外光照射下光催化制 取氢气的原理图 [39] Fig. 7 Schematic diagrams of photocatalytic H 2 production using BP-Au/LTO under (a)visible and (b)NIR light irradiation [39] 和 BP 受可见光和近红外光激发后将电子转移注入 LTO, 而 LTO 可以在甲醇牺牲剂存在下高效催化产 生 H 2 。 BP 和等离子体 Au 的宽光谱吸收以及激发的 BP 和 Au 向 La 2 Ti 2 O 7 的有效界面电子转移使其在可 见光区和近红外光区的光催化活性显著提高。 这些Ⅰ型、Ⅱ型、Z 型异质结光催化剂的设计 将为高效太阳能制氢体系的构建提供一条新的思路, 而上转换、等离子体共振效应的耦合作用也将对发 展全太阳光谱响应的高活性光催化剂具有重要的参 考价值 [40][41][42][43] 。 2 磷烯光催化分解水产氧和全水分解 反应 除产氢半反应外, BP 基材料还被应用于水的氧 化半反应。Yan 等 [44] [45] 构筑了 BP 和 BiVO 4 的 2D/ 2D 异质结构, 并构建了高效 Z 型光催化全水分解体 系(图 8)。 在没有任何牺牲试剂和外加偏压的情况下, 使用 BP/BiVO 4 异质结构光催化剂, 在可见光照射 图 8 可见光照射下 BP/BiVO 4 的 Z 型光催化裂解水系统原 理图 [45]…”
Section: 磷烯基异质结光催化剂的设计unclassified